Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.18632/oncotarget.3438
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-3127 promotes cell proliferation and tumorigenicity in hepatocellular carcinoma by disrupting of PI3K/AKT negative regulation

Abstract: Recent studies have shown that multiple phosphatases deactivate the PI3K/AKT signaling pathway. Here we demonstrated that, by suppressing multiple phosphatases, miR-3127 promotes growth of hepatocellular carcinoma (HCC). Our study also reveals clinical significance of miR-3127 expression in HCC patients. MiR-3127 expression was markedly upregulated in HCC tissues and cells. Furthermore, high miR-3127 expression was associated with an aggressive phenotype and poor prognosis. MiR-3127 overexpression promoted HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…In another study, miR-3127 was shown to repress NSCLC cell proliferation and invasion via the direct regulation of oncogene ABL1, leading to the inhibition of the RAS/ERK pathway (Sun et al, 2014). However, there were still conflicting reports that miR-3127 actually acted as an oncogene in hepatocellular carcinoma by activating AKT/FOXO1 signaling, via directly targeting the 3 -UTR of PHLPP1/2 (Jiang et al, 2015). The precise mechanisms of action and target genes of miR-3127 in BCA are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, miR-3127 was shown to repress NSCLC cell proliferation and invasion via the direct regulation of oncogene ABL1, leading to the inhibition of the RAS/ERK pathway (Sun et al, 2014). However, there were still conflicting reports that miR-3127 actually acted as an oncogene in hepatocellular carcinoma by activating AKT/FOXO1 signaling, via directly targeting the 3 -UTR of PHLPP1/2 (Jiang et al, 2015). The precise mechanisms of action and target genes of miR-3127 in BCA are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microRNAs (miRNAs) are small endogenous non-coding RNAs composed of approximately 19-24 nucleotides that regulate target genes posttranscriptionally (Dong et al, 2017), and miRNAs play key roles in the modulation of tumor growth and metastasis (Dong et al, 2017(Dong et al, , 2018b. It has been reported that miR-3127 acts as either a tumor suppressor or an oncogene in cancers, such as glioma (Pan et al, 2019), lung cancer (Sun et al, 2014;Yang et al, 2018) and hepatocellular carcinoma (Jiang et al, 2015). Downregulation of miR-3127-5p promotes epithelial-mesenchymal transition through activating the Wnt/FZD4/β-catenin pathway in nonsmall-cell lung cancer (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocellular carcinoma (HCC), miR-331-3p, which targets both PHLPP1 and PHLPP2, is significantly over-expressed [35]. miR-3127 is also over-expressed in HCC, and can function to suppress expression of not only PHLPP1 and PHLPP2, but also Inositol Polyphosphate Phosphatase 4A (INPP4A) and Inositol Polyphosphate-5-Phosphatase J (INPP5J) [36], two enzymes involved in inositol metabolism. miR-205 has been shown to target the 3′UTR of PHLPP2 and Phosphatase and Tensin Homologue (PTEN), and is in a region of the genome that is frequently amplified in non-small cell lung cancer (NSCLC) [37].…”
Section: Regulation Of Phlpp Expressionmentioning
confidence: 99%
“…PI3K is a kinase that is involved in multiple cellular signaling pathways. As regards Akt, it is an important factor in the downstream of PI3K (20). It is able to regulate cell proliferation and prevent cell apoptosis.…”
Section: Overexpression Of Microrna-133b Is Associated With the Incrementioning
confidence: 99%